Comparative Impact of Olanzapine and Aripiprazole on the Development of Metabolic Syndrome in Patients with Psychiatric Disorders: Olanzapine and Aripiprazole on the Metabolic Syndrome in Psychiatric Disorders Patients - Mafani, Suhail; Khan, Nadiya; Mansoor, Mehwish; Ali, Syed Liaquat; Anwar, Khawar; Islam, Ayesha (Pakistan Journal of Health Sciences, 2025)
To compare the development of metabolic syndrome in patients treated with olanzapine versus aripiprazole. Methods: This prospective observational study was conducted at Shahida Islam Medical College and Hospital over six months (June–November 2024). Patients with psychiatric disorders who had received either olanzapine or aripiprazole for ≥6 months were included. Metabolic syndrome was assessed using the International Diabetes Federation (IDF) criteria. Patients were divided into two treatment groups: olanzapine (n=104) and aripiprazole (n=104). Data were analyzed using SPSS version 23.0. Chi-square, Fisher’s exact, independent t, and Mann-Whitney U tests were applied where appropriate, with p<0.05 considered significant. Results: A total of 208 patients were analyzed (mean age: olanzapine 46.42 ± 9.21 years; aripiprazole 47.44 ± 8.78 years). Metabolic syndrome prevalence was significantly higher in the olanzapine group (45.2%) compared to the aripiprazole group (30.8%) (p<0.05). Patients on olanzapine had higher waist circumference, BMI, and blood pressure. Metabolic abnormalities were also more frequent with olanzapine: diabetes (34.0% vs. 15.6%), hyperlipidemia (25.5% vs. 9.4%), and microalbuminuria (25.5% vs. 6.3%). Conclusions: Aripiprazole demonstrated a significantly lower risk of metabolic syndrome and better metabolic outcomes than olanzapine, highlighting the need for careful monitoring and the consideration of safer alternatives in clinical practice.